To solve the compound inequality \(-3 \leq 2x - 5 < 1\), we can break it down into two parts:
- Solve \(-3 \leq 2x - 5\)
- Solve \(2x - 5 < 1\)
Step 1: Solve \(-3 \leq 2x - 5\)
Add 5 to both sides:
\[ -3 + 5 \leq 2x \] \[ 2 \leq 2x \]
Now, divide both sides by 2:
\[ 1 \leq x \quad \text{or} \quad x \geq 1 \]
Step 2: Solve \(2x - 5 < 1\)
Add 5 to both sides:
\[ 2x < 1 + 5 \] \[ 2x < 6 \]
Now, divide both sides by 2:
\[ x < 3 \]
Combine the Results
Now we combine the two parts of the compound inequality:
\[ 1 \leq x < 3 \]
This can be expressed in interval notation as:
\[ [1, 3) \]
Conclusion
The solution to the compound inequality \(-3 \leq 2x - 5 < 1\) is:
\[ x \in [1, 3) \]